Demystifying the Antecedents of Brand Advocacy : Mediating the Role of Brand Love and Brand Passion - Goswami, Susobhan; Balasubramanian, Nataraj (Indian Journal of Marketing, 2022)
This research aimed to analyze the antecedents of brand advocacy and investigate the mediating role of brand love and brand passion. This research used a structured questionnaire and an online survey to collect the responses. The proposed hypotheses were tested with covariance-based structural equation modeling. The mediation effect was investigated with the help of IBM-SPSS software. The antecedents of brand advocacy were identified to be brand trust, brand image, self-brand connect, and brand experience. The interesting finding of the research is that brand love and brand passion were found to have a mediating effect on the path model. The critical contribution of the research is that brand love was found to be the proximal mediator for antecedents, and brand passion was found to be the distal mediator in the path model. A brand manager’s primary task is to ascertain a brand’s features, propagate the brand story, and engage loyal customers of different platforms with love. This research will help brand managers to formulate targeted marketing strategies to promote brand advocacy.